Does interactivity require multimedia? The case of SAKI - Michael Horwood (Association for Learning Technology, 1993)
SAKI is a self-adaptive touch-typing tutor with a pedigree dating back to the mid-1950s. Even in its most recent form it eschews the temptation to present itself with the trimmings now commonly associated with microcomputer products. This paper argues that while the absence of such features may be a limiting factor in the commercial success of the program, SAKI is nevertheless a prime example of the way in which a computer can successfully react to and interact with a user, and indeed one which would actually lose educational value if it were to undergo an interface-lift. It should be noted that Eurotech is the official distributor of SAKI